2000
DOI: 10.1136/vr.146.5.117
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serological and sequencebased methods for typing feline calicivirus isolates from vaccine failures

Abstract: Feline calicivirus (FCV) can be typed by exploiting antigenic differences between isolates or, more recently, by the sequence analysis of a hypervariable region of the virus's capsid gene. These two methods were used to characterise FCV isolates from 20 vaccine failures which occurred after the use of a commercial, live-attenuated vaccine. Using virus neutralisation, the isolates showed a spectrum of relatedness to the vaccine; depending on the criterion adopted for identity, 10 to 40 per cent of them appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 35 publications
1
39
0
1
Order By: Relevance
“…As a result, it has not proved possible to identify groupings of FCV either on spatial (except possibly Japan), temporal or clinical grounds, and the virus is generally considered to exist as multiple strains that are all members of a single diverse genotype. The definition of "strain" is perhaps somewhat arbitrary, but has been defined by some as FCV isolates that are > 20% different based on nucleotide sequence of capsid region E [84,87,88].…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it has not proved possible to identify groupings of FCV either on spatial (except possibly Japan), temporal or clinical grounds, and the virus is generally considered to exist as multiple strains that are all members of a single diverse genotype. The definition of "strain" is perhaps somewhat arbitrary, but has been defined by some as FCV isolates that are > 20% different based on nucleotide sequence of capsid region E [84,87,88].…”
Section: Aetiologymentioning
confidence: 99%
“…Parenteral modified-live FCV vaccines have been associated with clinical signs in the immediate period postvaccination. Most of these appear to be due to coincidental infection with field virus although in some cases, sequence analysis has shown that vaccine virus may be involved [84,87]. Vaccine virus has also occasionally been detected circulating in the cat population, though the significance of this is not yet known [77,88,89].…”
Section: Vaccinesmentioning
confidence: 99%
“…To assign sequences to strains, we used the previously defined nucleotide distance threshold of 20% for hypervariable region E of the capsid (31,35). Pairwise genetic distances between sequences were calculated using the Jukes-Cantor approach as implemented in MEGAv4.0 (47).…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotide sequences of the variable and immunodominant regions C to E of the capsid gene (44) differ at more than 20% of sites when epidemiologically unrelated viruses are compared, and these are considered distinct strains (33). Epidemiologically related viruses such as those found in acute outbreaks of disease are usually less than 1 to 2% divergent (and rarely more than 5% divergent) and are considered variants of the same strain (31,35). However, during endemic infections, such as those that exist in some household colonies, variants of a single strain have been shown to vary by up to 18% (7).…”
mentioning
confidence: 99%
“…For PV, primers P6 (5Ј-CCTCCGGCCCCTGAATG-3Ј) and P7 (5Ј-ACCGGATGGCCAATCCAA-3Ј) were used to generate a 197-bp amplicon, as originally described by Jaykus et al (26). For feline calicivirus, primer 4 (5Ј-TTGCAACTGATTATATTGTTCCTGG-3Ј) and primer 5 (5Ј-GC AGTGTTGGATATTTTCTTGTCACC-3Ј) were used to generate a 243-bp amplicon, as originally described by Radford et al (41). For HAV, primers HAV 2949 (5Ј-TATTTGTCTGTCACAGAACAATCAG-3Ј) and 3192 (5Ј-AGGAGG TGGAAGCACTTCATTTGA-3Ј) were used to generate a 267-bp amplicon, as previously described (37,45).…”
Section: Vol 77 2011 Virus Detection and Persistence Within Hemocytmentioning
confidence: 99%